(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the attempt of search of the regularities of being of the traditions in time and the ways of movement of the culture in the ethnic purity rural commune living in the contrast national environment. The notions about ethno-cultural processes accepted in scientific school of J.V. Bromlej are subjected to criticism in it on the basis of empirical facts.